The Effect of Market Competition on the Price of Topical Eye Drops. (2nd January 2022) - Watane, Arjun; Kalavar, Meghana; Reyes, Joshua; Yannuzzi, Nicolas A; Sridhar, Jayanth
ABSTRACT: Purpose: To describe the relationship between the number of Federal Drug Administration (FDA)-approved manufacturers and the price change of generic and branded topical eye drops. Methods: Retrospective analysis of topical eye drop medications with formulations listed in the FDA Orange Book and the National Average Drug Acquisition Cost database from 2013 to 2017. Results: The most frequently prescribed generic topical drugs were glaucoma medications (34%), antimicrobials (32%), anti-inflammatories (24%), mydriatics (5%), and anesthetics (5%). The most frequently prescribed branded topical drugs were anti-inflammatories (45%), glaucoma medications (32%), antimicrobials (21%) and dry eye medications (3%). From 2013 to 2017, generic eye drops had a median price decrease of 20% (IQR 32%) while branded eye drops had a median price increase of 44% (IQR 28%) ( P < .001). A significant inverse association was identified between the price change of generic eye drops and the total number of all manufacturers (r = −.41, P = .010), generic drug manufacturers (r = −.32, P = .0496), and alternative branded drug manufacturers (r = −.57, P = .002). There was no significant association between the price change of branded eye drops and number of manufacturers. Glaucoma (r = −.58, P = .039) and anti-inflammatory (r = −.69, P = .047) eye drops also had significant inverse associations with the number of generic manufacturers. Conclusion: From 2013 to 2017, the price of generic eye drops decreased whereas the price of branded eye drops increased. Market competition was significantly inversely associated with price changes of generic eye drops but not branded eye drops.